Charakter narodowy a charakter organizacyjny - Jarosiewicz, Henryk (National character and organizational character, 2006)
The concept of character as an artefact i.e. a product of organizing one’s inner structure process (self-regulation, self-control) is presented. The character understood this way is shaped in the process of directing the behaviour. The national character and the organizational character are created analogically. The organizational character is shaped in the course of social learning - typical of the influence of company organizational culture and it coexists with the national character. The organizational character influences the national character in a modified way, whereas the national character enforces some changes in the field of the organizational culture of global enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 346-355